2011
DOI: 10.17221/255/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cronobacter spp. isolates from infant formulas and their survival in the production process of infant formula

Abstract: Fu S. , Gao J., Liu Y., Chen H. (2011): Isolation of Cronobacter spp. isolates from infant formulas and their survival in the production process of infant formula. Czech J. Food Sci., 29: 391-399.Over a 24-month surveillance, three Cronobacter strains, NC041, NC830, and NC1006, were isolated from 77 powder infant formulas (3.90%). No Cronobacter was detected in liquid milk. The prevalence of Cronobacter in the prefinal product and packaged final product was 3.70% and 4.35%, respectively. The isolated Cronobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…More importantly for neonatal health, Cronobacter spp. have been isolated from powdered infant formula (PIF) and milk powder production factories (11)(12)(13). Consequently, they can cause severe neonatal infections through the ingestion of contaminated PIF, especially in low-birth-weight infants (14,15).…”
mentioning
confidence: 99%
“…More importantly for neonatal health, Cronobacter spp. have been isolated from powdered infant formula (PIF) and milk powder production factories (11)(12)(13). Consequently, they can cause severe neonatal infections through the ingestion of contaminated PIF, especially in low-birth-weight infants (14,15).…”
mentioning
confidence: 99%
“…have been isolated from powdered infant milk formulae, infant cereals, vegetables, ready-to-eat food, dried products, spices, meat, and eggs (reviewed by Friedemann 2007). Cronobacter strains are resistant to dry stress and alkaline environments of up to pH 10 but do not survive acid stress (pH < 4.0) and heating (Fu et al 2011). An effective method is desirable for reducing Cronobacter in foods by using natural antimicrobial substances, such as bacteriocins, essential oils, or antimicrobial lipids.…”
mentioning
confidence: 99%
“…Edelson-Mammel et al (2006) showed that Enterobacter sakazakii (4.01C, 607, ATCC 29544, ATCC 51329, NQ1-Environ, NQ2-Environ, Environ NQ3, LCDC648, LCDC648, LCDC 674, CDC A3 (10), SK90, EWFAKRC11NNV1493) experienced a decrease in cells after 5 hrs of exposure to pH 3.0 and 3.5. Fu et al (2011) also found that Cronobacter NC041, NC1006, and NC830 could not survive at pH 3.0 and 3.5 (pH value <4.0) to 24 hrs of incubation. Additionally, Hsiao et al (2010) reported that C. sakazakii BCRC 13988 after 3 hrs of exposure to gastric acid simulations (pH 3.0) was more rapidly decreasing than that exposed to pH 3.5.…”
Section: Acid Stress Induction and Evaluation Of Cell Culture And Viamentioning
confidence: 92%